2020
DOI: 10.29252/jmp.19.74.343
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the essential oil composition of Ducrosia anethifolia (DC.) Boiss. in differnet altitudes of Sistan and Baluchestan province, Iran

Abstract: Background: The content and composition of effective components of medicinal plants in different natural habitats are affected by various factors such as elevation of sea level. Objective: The aim of this study was to investigate the effects of altitude of sea level on the essential oil composition of Ducrosia anethifolia Boiss in its natural habitats in Sistan and Baluchestan province, Iran. Methods: The plant aerial parts were gathered at full flowering stage from four different altitudes including altitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…There are also some s tudies in which decanal has not been reported as the major compound [3,28,29]. The results of Arbabi et al showed that cis-chrysanthenyl acetate with an average amount of 44.77% was the main compound of the essential oil of D. anethifolia from Si s tan & Baluchi s tan [2]. Besides, our results revealed that this technique had beneficial effects on the amount of phenolic and flavonoid contents and consequently on the antioxidant activity of the plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also some s tudies in which decanal has not been reported as the major compound [3,28,29]. The results of Arbabi et al showed that cis-chrysanthenyl acetate with an average amount of 44.77% was the main compound of the essential oil of D. anethifolia from Si s tan & Baluchi s tan [2]. Besides, our results revealed that this technique had beneficial effects on the amount of phenolic and flavonoid contents and consequently on the antioxidant activity of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Ducrosia has three species in Iran including D. anethifolia, D. assadii Alava, and D. flabellifolia Boiss. Ducrosia anethifolia grows wildly in mountainous and plain areas on sandy soils in different regions of Iran such as Kerman, Khorasan, Zanjan, Shushtar, Behbahan, Shiraz, Kazerun, Borazjan, Noorabad, Farashband, Firoozabad, Jahrom, Darab, and Si s tan Baluche s tan [2]. It also grows natively in countries from the Mediterranean range to W. Paki s tan such as Afghani s tan, Paki s tan, Iraq, Syria, Lebanon, and some Arab countries [3].…”
Section: Introductionmentioning
confidence: 99%